Thank you, Dr. Salk! : the scientist who beat polio and healed the world - Robbins, Dean, 1957- (Farrar Straus Giroux Books for Young Readers, an imprint of Macmillan Children's Publishing Group, LLC, 2021)
"A nonfiction picture book about Jonas Salk and the invention of the polio vaccine"--